Dynamic swimming pattern of Pseudomonas aeruginosa near a vertical wall during initial attachment stages of biofilm formation - Khong, Nicole Zi-Jia (2021)
Studying the swimming behaviour of bacteria in 3 dimensions (3D) allows us to understand critical biological processes, such as biofilm formation. It is still unclear how near wall swimming behaviour may regulate the initial attachment and biofilm formation. It is challenging to address this as visualizing the movement of bacteria with reasonable spatial and temporal resolution in a high-throughput manner is technically difficult. Here, we compared the near wall (vertical) swimming behaviour of P. aeruginosa (PAO1) and its mutants ΔdipA (reduced in swarming motility and increased in biofilm formation) and ΔfimX (deficient in twitching motility and reduced in biofilm formation) using our new imaging technique based on light sheet microscopy. We found that P. aeruginosa (PAO1) increases its speed and changes its swimming angle drastically when it gets closer to a wall. In contrast, ΔdipA mutant moves toward the wall with steady speed without changing of swimming angle. The near wall behavior of ΔdipA allows it to be more effective to interact with the wall or wall-attached cells, thus leading to more adhesion events and a larger biofilm volume during initial attachment when compared with PAO1. Furthermore, we found that ΔfimX has a similar near wall swimming behavior as PAO1. However, it has a higher dispersal frequency and smaller biofilm formation when compared with PAO1 which can be explained by its poor twitching motility. Together, we propose that near wall swimming behavior of P. aeruginosa plays an important role in the regulation of initial attachment and biofilm formation.